Lifetime Number of Mates Interacts with Female Age to Determine Reproductive Success in Female Guppies - Evans, Jonathan P. (PLOS ONE, 2012)
In many species, mating with multiple males confers benefits to females, but these benefits may be offset by the direct and indirect costs associated with elevated mating frequency. Although mating frequency (number of mating events) is often positively associated with the degree of multiple mating (actual number of males mated), most studies have experimentally separated these effects when exploring their implications for female fitness. In this paper I describe an alternative approach using the guppy Poecilia reticulata, a livebearing freshwater fish in which females benefit directly and indirectly from mating with multiple males via consensual matings but incur direct and indirect costs of mating as a consequence of male sexual harassment. In the present study, females were experimentally assigned different numbers of mates throughout their lives in order to explore how elevated mating frequency and multiple mating combine to influence lifetime reproductive success (LRS) and survival (i.e. direct components of female fitness). Under this mating design, survival and LRS were not significantly affected by mating treatment, but there was a significant interaction between brood size and reproductive cycle (a correlate of female age) because females assigned to the high mating treatment produced significantly fewer offspring later in life compared to their low-mating counterparts. This negative effect of mating treatment later in life may be important in these relatively long-lived fishes, and this effect may be further exacerbated by the known cross-generational fitness costs of sexual harassment in guppies.